2020
DOI: 10.1097/rlu.0000000000003175
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Presentation of COVID-19 Incidentally Detected at 18F-FDG PET/CT in an Asymptomatic Oncological Patient

Abstract: The incidence of COVID-19, a severe acute respiratory syndrome caused by SARS-CoV-2, is rapidly growing worldwide. In this pandemic period, the chance of incidental pulmonary findings suggestive of COVID-19 at 18F-FDG PET/CT in asymptomatic oncological patients is not negligible. To suspect COVID-19 is more demanding whether its presentation is atypical. We describe the incidental PET/CT detection of an 18F-FDG–avid isolated centrilobular pulmonary consolidation in an asymptomatic lymphoma patient, which later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…The mean ± SD SUVlbm max was 4.18±1.32 (min 3.24 and max 6.8). We note that there was no dissemination in other organs that might be attributed to COVID–19, fact similar mentioned by other authors [ 10 , 12 , 15 ].…”
Section: Discussionsupporting
confidence: 90%
“…The mean ± SD SUVlbm max was 4.18±1.32 (min 3.24 and max 6.8). We note that there was no dissemination in other organs that might be attributed to COVID–19, fact similar mentioned by other authors [ 10 , 12 , 15 ].…”
Section: Discussionsupporting
confidence: 90%
“…A number of studies published in the ensuing weeks concordantly reported similar incidental pulmonary findings in otherwise asymptomatic or mildly symptomatic patients who received 18 F-FDG PET/CT for oncologic indications, many of whom also demonstrated nodal involvement. 40 , 73 , 74 , 75 , 76 , 77 , 78 , 79 These and other reports were recently quantified in a systematic review by Rafiee et al which reported a mean SUV max of 4.9 ± 2.3 in COVID-19-associated pulmonary lesions. 11 Representative images of characteristic lesions are pictured in Figure 4 , Fig.…”
Section: Petmentioning
confidence: 82%
“…Over the last three months, a few case reports have also been published which describe asymptomatic nature of this disease in patients where this infection was detected incidentally. One of these reports describes an oncology patient in whom pulmonary findings concerning for COVID 19 were radiologically identified while undergoing workup for lymphoma [2].…”
Section: Discussionmentioning
confidence: 99%